DEVELOPMENT OF A RATING MODEL OF THE ASSESSMENT OF SCIENTIFIC PROJECTS - Pavel A. Kalachikhin; Yury F. Telnov (Статистика и экономика)
The procedure of organization of scientific projects competition in a higher education institution is investigated in the article. The method of expert evaluations is taken as a basis and the factorial variables are used at calculation. The rules of processing of model parameters, calculation of intermediate variables, calculation of a total rating and division of objects into classes on value of a rating are the results. The developed technique allows increasing validity of results of competitive selection during planning scientific researches.